Spherical magnetic flux flows with fractional Heisenberg spherical ferromagnetic spin of optical spherical flux density with fractional applications - Körpınar, Talat; Körpınar, Zeliha (World Scientific, 2021)
In this paper, we construct a new approach of spherical magnetic Lorentz flux of spherical Sα-magnetic flows of particles by the spherical frame in S2 spherical space. Eventually, we obtain some optical conditions of spherical Sα-magnetic Lorentz flux by using directional spherical fields. Moreover, we determine spherical magnetic Lorentz flux for spherical vector fields. Also, we give new construction for spherical curvatures of spherical Sαmagnetic flows by considering Heisenberg spherical ferromagnetic spin. The approximate solution is expressed by a table and some graphics. Finally, the magnetic flux surface is demonstrated in a static and uniform magnetic surface by using the analytical and numerical results. © World Scientific Publishing Company
Keywords: Geometric magnetic flux density; Heisenberg ferromagnetic spin; Spherical frame; Spherical Sα-magnetic flows